Peran Komite Sekolah Sebagai Advisory Agency Pendidikan Di SMA N 1 Pulau Beringin Muara Dua Okus - Mahesa Anugrah Akbar; Kris Setyaningsih; Dian Safitri (Jurnal Pendidikan Sosial Dan Konseling, 2023)
This thesis is entitled "The Role of the School Committee as an Educational Advisory Agency at SMA N 1 Pulau Beringin Muaradua OKUS". The background of this research is that school committees are still not optimal in carrying out their role as advisory agencies or giving considerations. Such as providing considerations in planning, providing considerations in implementation, providing considerations in terms of managing educational resources at SMA N 1 Pulau Beringin. The approach used is descriptive qualitative using a type of qualitative research to describe a problem regarding the role of the school committee as an educational advisory agency at SMA N 1 Pulau Beringin Muaradua OKUS. This research data collection technique uses observation, interviews and documentation. Meanwhile, data analysis techniques are data reduction, data presentation and drawing conclusions. Checking the validity of the data using source triangulation aims to test the credibility of the data by comparing the data that has been collected to describe it into categories, which views are the same and different from the data sources in conducting research on the role of the school committee as an educational advisory agency at SMA N 1 Pulau Beringin Muaradua OKUS. The research results show that the role of the school committee as an educational advisory agency at SMA N 1 Pulau Beringin Muaradua OKUS is carried out quite well. Judging from the indicators, the role of the school committee as an educational advisory agency is providing considerations, providing input on management, providing input on considerations. The implementation is considered to be quite good even though there are still shortcomings in the advisory agency. Therefore, advisory agencies or member considerations should be further improved in terms of planning, implementation and management, in order to achieve previously planned goals.